PENYULUHAN TENTANG PEMANFAATAN JUS WORTEL PADA LANSIA DENGAN HIPERTENSI - Zuliawati Zuliawati; Hariati Hariati; Meta Rosaulina; Siti Marlina; Lili Suryani Tumanggor (INSTITUT KESEHATAN DELI HUSADA, 2021)
Elderly is someone who has reached the age of 60 years and over, both men and women. With increasing age, the risk of developing hypertension is greater, especially among the elderly. Hypertension is a condition when the blood pressure in the blood vessels increases. One of the non-pharmacological treatments that can be done in lowering blood pressure is consuming carrot juice. The benefits of carrots can lower blood pressure, because carrots contain potassium. Potassium acts as a diuretic which can maintain the balance of blood pressure. The purpose of this community service activity is to find out the benefits of carrot juice in lowering blood pressure in the elderly with hypertension. The service was carried out on 15 elderly people who had hypertension. The service implementation team provided training on how to process carrot juice in Talun Kenas village, Deli Serdang. The team made a home visit as an evaluation of the service program. The outreach activities went smoothly. There were 7 patients asked about the counseling material. The importance of carrying out routine counseling activities to the elderly about other complaints suffered to improve their health status.